Synergistic outstanding strengthening behavior of graphene/copper nanocomposites. (1st November 2019) - Yoo, Sung Chan; Lee, Junho; Hong, Soon Hyung
Abstract: Graphene reinforced copper matrix (graphene/Cu) nanocomposite powders are fabricated by the molecular-level mixing process and consolidated by spark plasma sintering and pressureless sintering process followed by hot isostatic pressing for the full densification. The addition of 1.2% volume fraction of graphene in Cu matrix resulted in 1.9 and 1.3 times increase in yield strength and elastic modulus, respectively, in comparison to those of pure Cu fabricated by same sintering process. Homogeneous dispersion of graphene in Cu matrix and strong interfacial bonding between graphene and Cu matrix allowed outstanding mechanical properties which are similar to theoretically estimated values based on strengthening mechanisms. The strengthening mechanisms of graphene/Cu nanocomposites are quantitatively discussed in respect to grain boundary strengthening, load transfer and dislocation strengthening caused by mismatch in thermal expansion coefficient between graphene and Cu. It is demonstrated that graphene/Cu nanocomposites were strengthened mainly by load transfer mechanism and graphene induced grain boundary strengthening of Cu matrix. In addition, the rapid cooling rate during the spark plasma sintering process resulted in the dislocation strengthening in graphene/Cu nanocomposites.